Packet sniffing system / Chan Hai Chai - Chan , Hai Chai (2005)
Network security tool such as packet sniffing is a standalone system that use to monitoring and capture network traffic of computers in a LAN environment. lt is capable of filtering out a certain port, JP address and protocol and generates a network traffic graph. It is a useful tool for network administrator and network engineer to monitoring the network traffic. The aim of this project to build this security tool to monitoring a network. Trace and identifies misuse or computer, improve network manageability and overcome some network problem. This system call show the summary report alter the packet is captured from all the users in the network, that call make network administrator and network engineer easy to identify which users have use more bandwidth in the network. This system is target to be implementing in a small organization LAN such as Faculty of Computer Science and information Technology in University Malaya. The Waterfall with prototyping model is chosen as the methodology to develop this system. This system is a stand alone solution that needs special development tools and languages such as C#, Microsoft Access, Winpcap and some relevant tools. This system is developed using Object-Oriented Analysis and Design which provides a particularly fine basis for internal or structural design. The target users for this system are network administrator and network engineer. This system hope can achieve the objective of providing a user friendly packet sniffing system that easy to use and effective in assisting network administrator to perform their works.